An analysis of the role played by NGOs in promoting peace in Zimbabwe’s prisons: case study ZACRO 2008 tO 2017 - Choofamba, Fungai Sheba (Midlands State University, 2019)
Crime offenders need to require skills in different trades while in custody through rehabilitation services. This case study seeks to show whether rehabilitation programs available in prisons are best at serving the interests of both inmates and crime offenders. The population of the study consisted of 200 male inmates and 5 prison officers out of which twenty inmates and ten prison officers were randomly selected. The study traced how the prison system’s efforts to transform in line with regional declarations and regional instruments that promote peace. The study highlighted that drafted policies have not been followed by supportive activities to promote rehabilitation services in prisons.Agricultual activities and performing arts are the most popular programs at Kentucky prison which grew in popularity through the officer’s unilateral initiatives than through the assessed needs of inmates. The researchers recommended that crime offenders need rehabilitation services that equip them with relevant skills for employment or self-projects as well as to be functional citizens in the society. They mostly prefer training in trades that require mastery of skills. Rehabilitation programs must be informed by needs assessment done in a collaborative manner by officers, crime offenders and other stake holders. Strategies such as private public partnerships on prison rehabilitation programs must be adopted. Rehabilitation support must go beyond prison walls to also serve sustainable livelihoods for those that acquire skills while in prison.